Socioeconomic impact due to COVID-19: An empirical assessment. Issue 2 (March 2022) - Gupta, Vedika; Santosh, KC; Arora, Rameshwar; Ciano, Tiziana; Kalid, Khairul Shafee; Mohan, Senthilkumar
Highlights: Analyzed socio-economic impact: pre, during and post lockdown periods. Considering India, we observed the following: a Production: Halt in industrial production led to an approximately threefold increase in the unemployment rate. b Indexing (non-essential items): Capital goods and consumer durables dropped down to 7.1 and 5.1, respectively. c Fuel demand: Demand for fuel and related products dropped down by almost 50%. d Equity markets: They dropped abruptly even before the announcement of the lockdown. e Assets: Gold and silver were reliable as compared to equity markets. A socio-economic framework is presented to depict the policy-level interventions undertaken to mitigate upheaval induced by the pandemic. Our case study could represent other countries/regions of the world. Abstract: Starting from December 2019, the novel COVID-19 threatens human lives and economies across the world. It was a matter of grave concern for the governments of all the countries as the deadly virus started expanding its paws over neighboring regions of infected areas. The spread got uncontrollable, thereby leaving no choice for the nations but to impose and observe nationwide lockdown. The lockdown further sorely hit many sectors, which in turn impacted the economy. Manufacturing, agriculture, and the service sector - the three pillars of the economy - have been adversely affected giving a major slow down to the economy belonging to every nation. Several schemes and policies were introduced by different state and central governments to absorb the impact of subsequent lockdowns on individuals. In this paper, we present a then and now analysis of the economy using a socioeconomic framework focusing on factors- unemployment, industrial production, import-export trade, equity markets, currency exchange rate, and gold and silver prices. For all these, we consider India as a case study because the Indian sub-continent has a wide landscape and rich cultural heritage presenting itself as a potential hub for economic activities. A thorough assessment has been made for the period January 2020- June 2020. The assessment will be beneficial to observe the long-term impact of any infectious disease outbreak such as COVID-19 locally and globally.